2023
DOI: 10.1063/5.0139534
|View full text |Cite
|
Sign up to set email alerts
|

Molecular understanding of the Helmholtz capacitance difference between Cu(100) and graphene electrodes

Abstract: Unraveling the origin of Helmholtz capacitance is of paramount importance for understanding the interfacial structure and electrostatic potential distribution of electric double layers (EDL). In this work, we combined the methods of ab initio molecular dynamics and classical molecular dynamics, and modeled electrified Cu(100)/electrolyte and graphene/electrolyte interfaces for comparison. It was proposed that the Helmholtz capacitance is composed by three parts connected in series, usual solvent capacitance, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…A molecular mechanical energy model was used to reproduce electrolytes in simulation. 45,46 Although there may be an uncertainty between the potential in simulations and that in experiments, 47 the trend of ion distribution shown by these simulations should be qualitatively reliable.…”
mentioning
confidence: 83%
“…A molecular mechanical energy model was used to reproduce electrolytes in simulation. 45,46 Although there may be an uncertainty between the potential in simulations and that in experiments, 47 the trend of ion distribution shown by these simulations should be qualitatively reliable.…”
mentioning
confidence: 83%
“…The observed capacitance peak was correlated with the potential-dependent change in the surface coverage of chemisorbed water, highlighting the formation of a dipole between the metal and chemisorbed water as the primary cause for the increased capacitance. Additionally, a recent investigation of the graphene/water interface revealed that its Helmholtz capacitance is almost independent of the electrode potential in the absence of surface water chemisorption, providing further evidence of the critical role played by metal–water chemical interactions for the increase in interfacial capacitance.…”
mentioning
confidence: 86%
“…However, it has been generally observed that the double layer capacitance computed using FFMD is significantly lower than experimental values . This discrepancy has been attributed to the incorrect representation of the distribution of the surface excess charge with the point-charge model generally used in the FFMD method . Recently, Schwarz and co-workers demonstrated that artificially adjusting the plane of excess surface charge on Ag(111) based on the results from density functional theory (DFT) calculations can rectify the computed capacitance of the Ag(111)/NaF solution interface, resulting in a faithful reproduction of the experimental capacitance under negatively charged conditions.…”
mentioning
confidence: 99%
“…) and then aligning the electrostatic potentials in bulk water, 41 drastically reducing the computational resources. To date, this efficient cSHE method has been successfully applied to several metal/water [41][42][43][44] and semiconductor/water interfaces, 33,45,46 whereas its application to TiO 2 /water interfaces is few.…”
Section: Introductionmentioning
confidence: 99%
“…To avoid the expensive computation, Cheng and coworkers modified the cSHE method, in which the is obtained by calculating the deprotonation free energy of H 3 O + in a pure water box () and then aligning the electrostatic potentials in bulk water, 41 drastically reducing the computational resources. To date, this efficient cSHE method has been successfully applied to several metal/water 41–44 and semiconductor/water interfaces, 33,45,46 whereas its application to TiO 2 /water interfaces is few.…”
Section: Introductionmentioning
confidence: 99%